Interprofessional Communication Team for Caregivers of Patients Hospitalized in the COVID-19 Wards: Results From an Italian Experience - Carletto, Sara; Corezzi, Michele; Furmenti, Maria Francesca; Olivero, Elena; Rapicavoli, Paola; Rossello, Paola; Stanizzo, Maria Rosa; Bovero, Andrea (Frontiers in Medicine, 2021)
Background During the COVID-19 pandemic, emergency restrictions did not allow clinician family meetings and relatives’ visits. In Molinette Hospital, a new communication model between healthcare providers and families of COVID-19 affected patients was developed by a team of physicians and psychologists. The study’s aims were to investigate caregivers’ distress and to analyse their satisfaction with the communications provided. Methods A cross-sectional study was conducted among caregivers of patients of Molinette Hospital COVID wards. Between April and June 2020, all caregivers were contacted two weeks after the patient's discharge/death to assess their satisfaction with the communications received through an online survey. Results A total of 155 caregivers completed the survey. Caregivers’ distress level was found to be higher in women than men (p=.048) and in caregivers whose relative died compared to the caregivers whose relative was discharged (p<.001). More than 85% of caregivers defined communication “excellent”/“very good”; being male was associated with higher satisfaction levels than women (β = -.165, p=.046). Besides daily communication, 63 caregivers (40.6%) received additional support from a psychologist of the team. Conclusions To our knowledge, this is the first study presenting, in an emergency, a new model of communication provided by a team of physicians and psychologists, and analysing satisfaction with it. This model was highly appreciated by caregivers and it limited the discomfort caused by the restrictions on relatives’ visits. It would be interesting to further evaluate the possibility of extending a communication model that includes doctors and psychologists in routine clinical practice.